122k views
4 votes
Solve for b in the literal equation y = 11x + 11b

2 Answers

4 votes

Answer:

b = y/11 -x

Explanation:


y = 11x + 11b\\Move \: 11x\:to\:the \:left\:and\:change\:its\:sign\\\\y -11x =11b\\\\Divide\:both\:sides\:of\:the\:equation\:by\: 11\\(y)/(11) -(11x)/(11) = (11b)/(11) \\y/11 -x =b\\\\b = (y)/(11) - x

User Tom Brock
by
5.5k points
5 votes

Answer: b = y/11 - x

Step-by-step explanation: You have to isolate your variable by dividing each side of the equation by your factors that DO NOT contain any variable.

I hope this helps you out.

User Dmay
by
5.6k points